Making and breaking the grid : a graphic design layout workshop 2026-02-16T08:05:55+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Samara, Timothy (Rockport Publishers, 2023)

(untitled)
Making and Breaking the Grid: A Graphic Design Layout Workshop (Third Edition) is the ultimate resource for designers who want to understand the rules of the grid, so they can get better at breaking them